THE INTERVENTION OF THE PROFESSIONAL PHYSICAL EDUCATION IN SOCIAL PROJECTS WITH EMPHASIS ON SPORT (Fiep Bulletin - online, 2013)
The present study aimed through a literature review, giving reasons indicating how the Social Projects with an emphasis in sports emerged in brazilian society, concurrent participation in an intervention of the Professional Physical Education, knowing that this professional works in an area of human knowledge in consolidation, as has recent regulation and professional recognition, lacking in some optical scientific and technical knowledge. The arguments willing provided an understanding of the sports as a social phenomenon assumes substantial prominence in contemporary society when developed from a social perspective, especially in the representation of social projects which, in turn, enabled a new field for the Professional Physical Education. Notwithstanding the fostering this type of initiative, facilitated the consolidation of the professional, as by disseminating positive evaluative precepts during the development of sports, reached the imperious visibility event which contributed to its consolidation, recovery and acceptance in society.
Keywords: Public Policies; Professional Physical Education; Sports.